Anti-Dengue, Anti-Bacterial, and Cytotoxicity Effect of Psidium guajava Fruit Extract - Soares, Engracia Natalia Desena; Sucipto, Teguh Hari; Susetyo, Rizky Danang; Agustini, Rudiana; Damayanti, Mamik; Herdyastuti, Nuniek; Setyawati, Harsasi; Setyarini, Wahyu; Ansori, Arif Nur Muhammad; Hariyono, Hariyono (Institute of Topical Disease Universitas Airlangga, 2026)
One of the main public health issues with increasing morbidity and mortality rates in tropical countries like Indonesia is dengue hemorrhagic fever (DHF). Antiviral treatments are still unobtainable and the curative value of current vaccines is limited. Many bioactive compounds, including flavonoids and tannins, identified in the tropical fruit Psidium guajava, which are utilized extensively in traditional medicine, have shown possible antiviral, antibacterial, and antioxidant effects. The focus of this research is to determine Psidium guajava extract's antiviral activity against DENV-1, cytotoxic effects on Vero cells, and antibacterial activity towards Escherichia coli. The extract was tested on DENV-1 in Vero cells using the Viral ToxGloTM assay, and the selectivity index (SI) was determined by using the IC50. The CellTiter 96Ò Aqueous One Solution Cell Proliferation Assay method was applied for cytotoxicity tests, while the disc diffusion method on Mueller-Hinton Agar was utilized for testing the antibacterial effect towards Escherichia coli. With an IC50 value of 67.74 µg/mL, the findings suggest that guava extract effectively inhibits DENV-1 replication. The level of cytotoxicity of this extract against Vero cells showed a good result, namely <200 µg/mL, which can be categorized as moderate cytotoxicity. Also, the Psidium guava extract indicated antibacterial effect against Escherichia coli, at a concentration of 100 mg/mL with an inhibition zone of 4.6 to 5.0 mm. Based on these findings, Psidium guajava extract has the potential to be a natural therapeutic substance with a good safety record towards antiviral, cytotoxicity and antibacterial effects.